The Effects of Water Salinity on the Freshwater Aquaculture Fish Survival - Dwimei Ayudewandari Pranatami; Indy Naurah Atiqah; Refi Mariska (Al Kawnu : Science and Local Wisdom Journal, 2026)
Indonesia, as a maritime country, has a high diversity of fish species. Fish play an important role as a source of protein for human consumption. To achieve optimal growth, fish require appropriate environmental conditions, one of which is water salinity. Proper salinity levels help fish maintain energy efficiency in metabolic processes and daily activities. Freshwater fish are widely cultivated due to their relatively simple farming methods.This study aims to determine the salinity levels that support optimal growth and examine their effects on the survival of freshwater aquaculture fish. The method used is a descriptive approach based on a literature review of various scientific journal articles discussing salinity and freshwater fish survival.The analysis shows that freshwater fish exhibit higher adaptability and survival rates at salinity levels of 5–10 ppt. In contrast, high salinity levels (32–35 ppt) can lead to significant mortality. Salinity levels between 10–30 ppt may still support survival but tend to result in slower growth. Appropriate salinity is essential for regulating osmotic pressure in fish body fluids, thereby ensuring optimal physiological function.   ABSTRAK Indonesia yang merupakan negara bahari yang kaya akan keanekaragaman ikan. Ikan memiliki potensi yang beraneka ragam terutama untuk dikonsumsi sebagai sumber protein. Penelitian ini bertujuan untuk mengetahui kisaran salinitas yang mendukung pertumbuhan optimal serta pengaruhnya terhadap kelangsungan hidup ikan air tawar. Metode yang digunakan adalah deskriptif melalui studi literatur terhadap berbagai artikel jurnal ilmiah yang membahas hubungan salinitas dengan pertumbuhan dan tingkat kelangsungan hidup ikan budidaya air tawar. Hasil kajian menunjukkan bahwa ikan air tawar memiliki tingkat adaptasi dan nilai Survival Rate (SR) yang tinggi pada kisaran salinitas 0–10 ppt. Pada salinitas 10–30 ppt, ikan masih mampu bertahan hidup, namun mengalami pertumbuhan yang terhambat. Sementara itu, salinitas tinggi pada kisaran 32–35 ppt menyebabkan peningkatan mortalitas secara signifikan. Kesimpulannya, pengaturan salinitas yang tepat sangat penting dalam budidaya ikan air tawar karena berperan dalam menjaga keseimbangan tekanan osmotik cairan tubuh, sehingga proses fisiologis dapat berlangsung secara optimal dan mendukung pertumbuhan serta kelangsungan hidup ikan.